Relationships between plasma lipidomic profiles and brown adipose tissue density in humans - Fuse, Sayuri; Sugimoto, Masahiro; Kurosawa, Yuko; Kuroiwa, Miyuki; Aita, Yasuko; Tomita, Atsumi; Yamaguchi, Eri; Tanaka, Riki; Endo, Tasuki; Kime, Ryotaro; Hamaoka, Takafumi (International Journal of Obesity, 2020)
Background/objectives The thermogenic function of brown adipose tissue (BAT) is generally activated in winter and tightly regulated through various metabolic processes. However, the mechanisms mediating these changes have not been elucidated in humans. Here, we investigated the relationships between BAT density (BAT-d) and lipid metabolites in plasma from men and women in the winter and summer. Subjects/methods In total, 92 plasma samples were obtained from 23 men and 23 women, aged 21–55 years, on two different occasions (summer and winter). Lipid metabolites were comprehensively quantified using liquid chromatography-time-of-flight-mass spectrometry. BAT-d was evaluated by measuring total hemoglobin concentrations in the supraclavicular region using near-infrared time-resolved spectroscopy. Anthropometric parameters, such as the percentage of whole body fat and visceral fat area (VFA), were evaluated. Factors influencing BAT-d were investigated by univariate and multivariate regression analyses. Results A variety of metabolite peaks, such as glycerophospholipids (168 peaks), steroids and derivatives (78 peaks), fatty acyls (62 peaks), and glycerolipids (31 peaks), were detected. Univariate regression analysis, corrected by false discovery rate to yield Q values, revealed significant correlations in BAT-d and phosphatidylethanolamine (PE(46:2), r = 0.62, Q = 4.9 × 10 −2 ) in the summer, androgens ( r = 0.75, Q = 7.0 × 10 −3 ) in the winter, and diacylglycerol (DG(36:1), r = −0.68, Q = 4.9 × 10 −2 ) in the summer in men, but not in women. Multivariate regression analysis in the winter revealed a significant correlation between BAT-d and plasma androgens ( P = 5.3 × 10 −5 ) in men and between BAT-d and VFA ( P = 2.2 × 10 −3 ) in women. Conclusions Certain lipids in plasma showed unique correlations with BAT-d depending on sex and season. BAT-d showed a specific correlation with plasma androgens in men in the winter.